Interleukin-1 receptor antagonist anakinra in association with remdesivir in severe COVID-19: A case report. (August 2020) - Franzetti, Marco; Pozzetti, Ugo; Carugati, Manuela; Pandolfo, Alessandro; Molteni, Chiara; Faccioli, Paolo; Castaldo, Gioacchino; Longoni, Ernesto; Ormas, Valentina; Iemoli, Enrico; Piconi, Stefania
Highlights: Severe COVID-19 infection is characterized by inflammatory dysregulation and cytokine storm. We report a case of clinical improvement after treatment with anakinra in association with remdesivir. The high tolerability, short half-life and immunomodulatory profile of anakinra may be useful in such a setting. Further studies are needed to confirm the safety and efficacy of anakinra in this setting. Abstract: We report the first successful treatment with the IL-1 receptor antagonist anakinra, in association with the most promising and available antiviral therapy, of a severe case of novel coronavirus disease 2019 (COVID-19). We describe the diagnosis, clinical course, and management of the case, including the respiratory failure at presentation, the progression to a scenario characterized by profound inflammatory dysregulation similar to that observed during macrophage activation syndrome, and the clinical improvement after treatment with the IL-1 receptor antagonist anakinra. This case highlights the high tolerability and the interesting immunomodulatory profile of the IL-1 receptor antagonist anakinra in the setting of severe COVID-19 associated with remdesivir therapy. Further studies are needed to confirm the safety and efficacy of this combination strategy in the treatment of this emerging infection.